GROWTH RESPONSE OF GREEN BEANS (Phaseolus radiatus) TO WATERING INTERVALS - Panggabean, Nurul Huda; Yudha Pratama, Rizky; Rahmadina, Rahmadina; Faisal Nasution, Ahmad; Situmorang, Nurbaity; Kairani, Anita (Universitas Negeri Medan, 2026)
Green beans (Phaseolus radiatus) are one of the commodity of legume plants that are generally grown on dry land, Green beans are included in plants that are tolerant of water shortages, the important thing is that the soil has enough moisture. The problem that is often faced in mung bean cultivation in dry land is the low production achieved by farmers, so it is necessary to conduct research on the resistance of mung beans (Phaseolus radiatus) to drought and the effect of watering frequency on productivity. The purpose was to determine the watering interval to the growth response of mung bean plants (Phaseolus radiatus). This study used an experimental design using a Group Random Design (RAK) consisting of 4 treatments with 3 replicas of each treatment. F0U1, F0U2, F0U3 : Control Treatment (No Watering), F1U1, F1U2, F1U3 : Watering frequency 1 (one) time a day. F2U1,F2U2, F2U3 : Watering frequency 2 (two) times a day. F3U1, F3U2, F3U3 : Watering frequency 3 (three) times a day. The parameters in calculating the growth response are the length of the plant, the number of leaves and the height of the plant. The best watering interval for plant length is watering once every 1 (one) day, where the highest plant length is 56.16 cm in the F1 treatment. The best watering interval for the number of leaves of the plant is watering (once) a day, where the average number of leaves is 13.11 leaves in the F1 treatment. The best watering interval for plant height is watering once every 1 (one) day, where the average height of the highest plant is 51.16 cm in the F1 treatment.